Memory and perception, insights at the interface: editors’ introduction (2021)
ABSTRACT: The recent development of specialized research fields in philosophy of memory and philosophy of perception invites a dialogue about the relationship between these mental capacities. Following a brief review of some of the key issues that can be raised at the interface of memory and perception, this introduction provides an overview of the contributions to the special issue, and outlines possible directions for further research.